Correlation of intact parathormone levels with serum calcium, serum phosphorus and serum vitamin d levels in surgical patients - Nilkamal Kumar; Nita Garg; Ishita Gupta (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2017)
Aim: The aim of our study was to determine a correlation between hyperparathyroidism and Serum Calcium, Phosphorus and Vitamin D levels.Study Design: A Hospital based cross-sectional study was conducted on the patients attending the Out patient Department of Surgery, of SGRR Medical College, Dehradun (UK), during a period of 6 months from November 2016 to April 2017. A total number of 66 cases (32 male + 34 female) and 45 controls (20 male +25female) in the age group of 20-60 years were selected randomly for this study. Exclusion criteria were age less than 20 years and more than 60 years, pregnancy, diabetes, tuberculosis etc.Methodology: The blood samples were collected in fasting state and Serum iPTH, Vitamin-D, Calcium & Phosphorus levels were estimated on a fully automated machine 5600 of Orthodiagnostics.Results: The levels of iPTH were found to be higher in female cases than male cases and much higher when compared with controls both male & female. Both male & female hyper parathyroid cases were normocalcemic. Vitamin D levels were found to be lower in both male & female cases as compared to their normal counterparts. Serum Phosphorus levels were found to be on the lower side in both cases as compared with normal controls.